PENGARUH INTERAKSI EDUKATIF GURU SERTA DISIPLIN BELAJAR SISWA TERHADAP HASIL BELAJAR BAHASA ARAB - Basith, Abdul; Nur Imamatun Nisa’ (BASA Journal of Language & Literature, 2024)
This study examines how student learning discipline and teacher-student interactions affect Arabic language learning results at SMP Queen Ibnu Sina Genteng in the 2023–2024 academic year. The study uses a pretest-posttest control group and a quasi-experimental approach. Purposive sampling strategies were used to choose 30 students for the experimental group and another 30 students for the control group. The Arabic language learning outcome is the dependent variable, whereas educational interaction and student learning discipline are the independent variables. The Wilcoxon Signed Rank Test and Mann-Whitney U Test (significance level of 0.05) are used to analyze the data from the interaction and learning discipline assessments that are part of the study instruments. The findings show that learning discipline and educational engagement have a major impact on Arabic language learning outcomes. The two variables have a positive association, as indicated by the Paired Sample T-Test's significant value of 0.000 (<0.05). The students performed well, as evidenced by their average Arabic language acquisition outcome of 96.33. To sum up, learning discipline and teacher-student interaction are essential to improving Arabic language learning results at SMP Queen Ibnu Sina Genteng. signifikan interaksi edukatif serta disiplin belajar terhadap hasil belajar bahasa Arab . Uji Paired Sample T - Test menampilkan nilai signifikan 0 , 000 ( <0 , 05 ) , sehingga ada ikatan positif antara kedua variabel tersebut . Hasil belajar bahasa Arab rata - rata siswa menggapai 96 , 33 , menampilkan hasil yang baik . Akhirnya , interaksi edukatif guru serta disiplin belajar berfungsi berarti dalam tingkatkan hasil belajar bahasa Arab di SMP Queen Ibnu Sina Genteng